Structural modelling of investment and financial constraints: Where do we stand? - Jean-Bernard Chatelain (National Bank of Belgium, 2002)
This paper surveys issues with respect to the structural modelling of econometric tests of investment facing financial constraints, to their link with firms data and assets prices, and to their impact in macroeconomic modelling. The key issue is to ground much more the interpretation of the sensitivity of investment to liquidity variables such as cash flow as a measure of financial constraints. The structural modelling of investment facing financial constraints is also limited by the structural modelling of the force driving investment dynamics such as adjustment costs, which has not been so successful empirically.
Keywords: D92; 330; Betriebliche Liquidität; Investitionsentscheidung; Cash Flow; Theorie